2001
DOI: 10.1046/j.1365-2222.2001.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA‐A, B alleles and polymorphisms of TAP and LMP genes in Korean patients with atopic dermatitis

Abstract: This study demonstrates an association of atopic dermatitis with HLA-A24 and TAP2*C alleles in Korean patients. Discrepancy with the previous reports might be related to different patient characteristics and ethnic variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Lee et al studied Korean patients and showed an association with HLA-A24 antigen. 84 Saeki et al, in Japan, verified a high frequency, although not significant, of HLA-A24, -A33, -Cwblank, -B44, -DR13 antigens and HLA-DRB1*1302, -DQB1*0604 and -DPB1*0301 and reduced frequency of HLA-Cw1, -Bw6, -DR4, and -DR53 antigens and of HLA-DQ1*0302 allele. 86 In another study, this same group showed the association between amino acid epitopes in class II HLA molecules and severe AD accompanied by high serum levels of IgE.…”
Section: Atopic Dermatitismentioning
confidence: 93%
See 1 more Smart Citation
“…Lee et al studied Korean patients and showed an association with HLA-A24 antigen. 84 Saeki et al, in Japan, verified a high frequency, although not significant, of HLA-A24, -A33, -Cwblank, -B44, -DR13 antigens and HLA-DRB1*1302, -DQB1*0604 and -DPB1*0301 and reduced frequency of HLA-Cw1, -Bw6, -DR4, and -DR53 antigens and of HLA-DQ1*0302 allele. 86 In another study, this same group showed the association between amino acid epitopes in class II HLA molecules and severe AD accompanied by high serum levels of IgE.…”
Section: Atopic Dermatitismentioning
confidence: 93%
“…83 Since HLA molecules participate in the presentation and recognition of allergens in the immune response, class I and II HLA antigens are presumed to be involved with the pathogenesis of dermatitis and other atopic disorders. 84,85 Based on these data, several studies were performed seeking associations between atopies and the HLA system. 85 Some studies suggested an association with HLA genes.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…(69) The 565Ala and 665Thr alleles of the TAP2 gene may be associated with susceptibility to AD in a Korean population. (69) …”
Section: -Mhc (Or Hla) Genesmentioning
confidence: 99%
“…Human leukocyte antigen class-I (HLA-I) sub-classified as A, B, and C, are produce by all human cells except erythrocytes and trophoblasts The HLA group of genes located at chromosome 6p21.3. Eleven HLA-A (1, 2, 3 (69) The 333 Val and 637 Gly alleles of the transporter for antigen presentation 1 (TAP1) gene were significantly associated with susceptibility to AD among Tunisians population, (70) while allelic frequencies of the TAP1 gene polymorphisms were not associated with the disease. (69) The 565Ala and 665Thr alleles of the TAP2 gene may be associated with susceptibility to AD in a Korean population.…”
Section: -Mhc (Or Hla) Genesmentioning
confidence: 99%
“…The locus of HLA class II where they reside, however, is controversial Á DPB1 and DQB1 loci [3] or others (DQB1 and DRB1 loci, DQ-DP loci, DM-DQ loci). To clarify the contribution of TAP polymorphisms to allergic rhinitis, we determined the frequency of TAP1 (I333V) and TAP2 (A565T and R651C) polymorphisms in a Turkish population with allergic rhinitis.…”
Section: Background and Studymentioning
confidence: 99%